2004
DOI: 10.1093/fampra/cmh721
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with a GP and patients' evaluations of care. A cross-sectional study

Abstract: Familiarity with a GP improves patients' assessment of general practice care. Also in the future, personal continuity should be promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 8 publications
6
55
0
5
Order By: Relevance
“…At the same time, higher level of depersonalisation and feeling of professional ineffectiveness was associated with more years working at the current position. Although there is a lot of evidence that interpersonal continuity of care contributes to therapeutic doctor-patient relationship and positive outcomes of care (20,22,41,42), some negative emotional effects have also been recognised, such as frustration, boundary issues, and negative effects on personal life (43). Burnout rates in older surgeons in a study by Campbell et al (40) were lower due to greater job satisfaction and perceived sense of control and autonomy in practice (40).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, higher level of depersonalisation and feeling of professional ineffectiveness was associated with more years working at the current position. Although there is a lot of evidence that interpersonal continuity of care contributes to therapeutic doctor-patient relationship and positive outcomes of care (20,22,41,42), some negative emotional effects have also been recognised, such as frustration, boundary issues, and negative effects on personal life (43). Burnout rates in older surgeons in a study by Campbell et al (40) were lower due to greater job satisfaction and perceived sense of control and autonomy in practice (40).…”
Section: Discussionmentioning
confidence: 99%
“…24 Seeing a familiar GP has been related to higher levels of satisfaction and trust. 41 A study of African American patients found that a stated barrier to developing a trusting relationship with a physician was having to change physicians frequently. 42 A Swiss study found that trust was the number one reason patients remained with a particular practice.…”
Section: Trust and Confidencementioning
confidence: 99%
“…The result of this study again underline the value of this. Patients expect continuity of care of their GP (8). Continuity of care for the whole family will continue to lend additional value.…”
Section: Discussionmentioning
confidence: 99%